Balance, gait, and navigation performance are related to physical exercise in blind and visually impaired children and adolescents - Ann Kathrin Rogge and Daniel Hamacher and Giulia Cappagli and Laura Kuhne and Kirsten Hötting and Astrid Zech and Monica Gori and Brigitte Röder (Experimental brain research, 2021)
Self-motion perception used for locomotion and navigation requires the integration of visual, vestibular, and proprioceptive input. In the absence of vision, postural stability and locomotor tasks become more difficult. Previous research has suggested that in visually deprived children, postural stability and levels of physical activity are overall lower than in sighted controls. Here we hypothesized that visually impaired and blind children and adolescents differ from sighted controls in postural stability and gait parameters, and that physically active individuals outperform sedentary peers in postural stability and gait parameters as well as in navigation performance. Fourteen blind and visually impaired children and adolescents (8–18 years of age) and 14 matched sighted individuals took part. Assessments included postural sway, single-leg stance time, parameters of gait variability and stability, self-reported physical activity, and navigation performance. Postural sway was larger and single-leg stance time was lower in blind and visually impaired participants than in blindfolded sighted individuals. Physical activity was higher in the sighted group. No differences between the group of blind and visually impaired and blindfolded sighted participants were observed for gait parameters and navigation performance. Higher levels of physical activity were related to lower postural sway, longer single-leg stance time, higher gait stability, and superior navigation performance in blind and visually impaired participants. The present data suggest that physical activity may enhance postural stability and gait parameters, and thereby promote navigation performance in blind and visually impaired children and adolescents.
Keywords: Physical activity; Postural control; Spatial cognition; Vestibular system; Visual deprivation